The Judge Mediator in Contemporary Divorce Cases in Indonesian Religious Courts - Marzuqin, M. Akmal; Saini, Saini; Safithri, Awaliya Safithri; Miftahussurur, Wildan (USRATY : Journal of Islamic Family Law, 2025)
This study aims to analyze the role of the judge as a mediator in the resolution of divorce cases in Indonesian Religious Courts, focusing on the effectiveness and challenges faced in the mediation process. Using a qualitative approach, the study collects data through in-depth interviews with judges, mediators, and parties involved in divorce cases, as well as an analysis of relevant legal documents. The findings show that judges play a central role in the mediation process, both as neutral facilitators and as active mediators who can influence the final decision. However, the success of mediation largely depends on the mediator's skills, understanding of the existing laws, and the willingness of the parties to cooperate in the mediation process. Additionally, there are challenges related to the limited training of judges in mediation skills and the lack of clarity in some legal aspects governing mediation in Religious Courts. The study concludes that to improve the effectiveness of mediation in divorce cases, it is necessary to enhance judges' capacities through specialized training and to refine regulations that support better mediation practices. The academic contribution of this research is to provide a deeper understanding of the dynamics of the judge’s role as a mediator in family law contexts and to suggest policies that could enhance mediation practices in Indonesian Religious Courts for more peaceful and fair resolutions.